Mexico : Financial Sector Assessment Program Update; Technical Note; Financing of the Private Sector. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This technical note on financing of the private sector for Mexico describes the evolution, composition, and determinants of financing to the nonfinancial private sector in Mexico between 2000 and 2005. Equity issuance has not played an important role in financing the private sector in Mexico during 2000-05. The number of nonfinancial private sector issuers actually declined from 173 in 2000 to 155 at the end of 2005. The stock market displays a high level of concentration, with the top 10 companies representing close to 70 percent of market capitalization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet